Global Asymptotic Stability for Nonlinear Functional Integral Equation of Mixed Type - Zhinan Xia (Journal of Applied Mathematics)
The existence results of global asymptotic stability of the solution are proved for functional integral equation of mixed type. The measure of noncompactness and the fixed-point theorem of Darbo are the main tools in carrying out our proof. Furthermore, some examples are given to show the efficiency and usefulness of the main findings.